Your turn Marisol Rainey - Kelly, Erin Entrada (2025)
Will Marisol be brave today? Under normal circumstances, maybe. But in school, well... When it's Marisol's turn to score a point in gym, there's a good chance she won't. And if it's Marisol's turn to ask a question in class (even though she thought of a perfect one), she probably won't. Now it's Marisol's turn to stand up in front of everyone and recite the poem she wrote. There is no way she is brave enough for that. Or is she? Take your turn, Marisol Rainey!